Hverjir ávísa geðlyfjum utan sjúkrahúsa? : lyfseðlakönnun í Reykjavík í mars 1984 - Tómas Helgason; Júlíus Björnsson (Læknafélag Íslands, Læknafélag Reykjavíkur, 2010)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn Skoða/Opna(view/open) The distribution of doctors prescribing psychotropic drugs during one month in 1984 is analysed according to speciality and age, which drugs they prescibed, to whom, how and in what dosage. Psychiatrists issued only 17% of the prescriptions to 12.3% of the patients. General practitioners issued 55% of the prescriptions to 62.5% of the patients. Slightly more than 85% of the prescriptions were for tranquillizers and hypnotics. However, only 60% of the psychiatrists' prescriptions were for such drugs. Almost one half of the prescriptions included other drugs along with the psychotropics. General practitioners issued about 55% of their prescriptions by telephone, while psychiatrists issued only 15% of their prescriptions in that manner The psychiatrists treated relatively younger people. They advised their patients to take the drugs on an average in larger dosages than other doctors. All other doctors advised their patients to take on an average less than one defined daily dosis per day. The oldest doctors issued more prescriptions than the younger ones for greater amount of drugs each, but the prescribed dosis did not vary according to age. It would probably be possible to reduce the consumption of tranquillizers if other doctors did not issue more prescriptions than the psychiatrists by telephone. Í greininni er fjallað um hvernig þeir læknar, sem ávísuðu geðlyfjum á einum mánuði 1984, skiptust eftir sérgreinum og aldri, hvaða lyfjum þeir ávísuöu, hverjum, hvernig og í hve stórum skömmtum. Aðeins 17% ávísananna voru frá geðlæknum handa 12,3% sjúklinganna, en 55% ávísananna voru frá heimilislæknum handa 62,5% sjúklinganna. Rúm 85% ávísananna voru á róandi lyf eða svefnlyf, en ekki nema tæp 60% ávísana geðlækna. Tæpur helmingur lyfseðlanna var með öðrum lyfjum jafnframt. Heimilislæknar símsendu yfir helming ávísana sinna, en geðlæknar um 15%. Geðlæknar höfðu hlutfallslega fleiri yngri sjúklinga en aðrir ...